Pumpkin Soygurt Improves Blood Glucose Homeostasis in Diabetes Mellitus Rats Model - Avelia, Annisa; Tamtomo, Didik Gunawan; Sari, Yulia (Jurnal Gizi dan Pangan, 2023)
The study aimed to analyze the effect of pumpkin yogurt on insulin resistance in a rat model. The experiment employed 30 male Wistar rats divided into six groups: three control groups (healthy, negative, and positive) and three treatment groups (metformin+PS 1 mL, 1.5 mL, 2 mL). The experiments were conducted for four weeks. Blood glucose homeostasis was measured by fasting blood glucose, insulin, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), and Quantitative Insulin-Sensitivity Check Index (QUICKI). Administrating a combination of metformin and pumpkin soygurt can control blood glucose homeostasis with an effective dose of 1 mL. Further research should be done on the hormone incretin, which plays a role in insulin secretion.